2016
DOI: 10.1097/mnh.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of mitochondrial oxidative stress to hypertension

Abstract: Purpose of review In 1954 Harman proposed the free radical theory of aging, and in 1972 he suggested that mitochondria are both the source and the victim of toxic free radicals. Interestingly, hypertension is age-associated disease and clinical data show that by age 70, 70% of the population has hypertension and this is accompanied by oxidative stress. Antioxidant therapy however is not currently available and common antioxidants like ascorbate and vitamin E are ineffective in preventing hypertension. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 95 publications
(119 reference statements)
2
29
0
2
Order By: Relevance
“…This biosynthetic pathway is regulated by tyrosine hydroxylase, which is an enzyme positively controlled by mitochondrial activity . Excessive action of mitochondria constitutes an oxidative stress . In our study, the elevated level of noradrenaline found in patients with GAgP may be the result of biochemical abnormality of tyrosine metabolism; in conditions of high mitochondrial function, the activity of hydroxylase increases, resulting in an accumulation of noradrenaline.…”
Section: Discussionmentioning
confidence: 52%
“…This biosynthetic pathway is regulated by tyrosine hydroxylase, which is an enzyme positively controlled by mitochondrial activity . Excessive action of mitochondria constitutes an oxidative stress . In our study, the elevated level of noradrenaline found in patients with GAgP may be the result of biochemical abnormality of tyrosine metabolism; in conditions of high mitochondrial function, the activity of hydroxylase increases, resulting in an accumulation of noradrenaline.…”
Section: Discussionmentioning
confidence: 52%
“…43 All these metabolic conditions increase mitochondrial acetylation and risk of hypertension. 19, 4448 We suggest that imbalance between mitochondrial acetylation and reduced Sirt3 activity as a potential mechanistic link between metabolic conditions and hypertension.…”
Section: Discussionmentioning
confidence: 88%
“…44 It is therefore interesting to speculate that SOD2 hyperacetylation can be used as an integrative marker of mitochondrial impairment which can be beneficial as a prognostic factor in hypertension. Indeed, our animal data show positive correlation of severity of hypertension with SOD2 acetylation (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the missense mutation in PNPT1 (rs782572) that is associated with methylation level of mt-RNR2 (position 2617), is in high LD with rs197548, which is associated with systolic and diastolic blood pressure (Ehret et al 2016). Mitochondria have previously been linked to increased blood pressure, predominantly through mechanisms involving mitochondrial oxidative stress, however the exact mechanisms by which this is the case remain unclear (Dikalov and Dikalova 2016). We have previously observed associations between nuclear genetic variants influencing the expression of certain mitochondrial genes, mediated through the expression of PNPT1 (Ali et al 2019), and the identification of the overlap here suggests that RNA methylation level may also be playing a contributory role in the process.…”
Section: Overlap With Disease Associated Locimentioning
confidence: 99%